Exploring the concept of Indonesia traditional food sustainability / Yusup Apriyanto ... [et al.] - Apriyanto, Yusup; Md Sharif, Mohd Shazali; Mohd Shahril, Aslinda; Ishak, Noriza; Hashim, Nurul Falah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Sustainability and traditional food intertwine as cornerstones of a resilient and harmonious food ecosystem. Embracing traditional culinary practices not only preserves cultural heritage but also fosters environmentally conscious production and consumption, paving the way toward a more sustainable future. This research aims to explore the concept of traditional food sustainability through the literature study. It found that traditional food sustainability encompasses the preservation of production, consumption, and cultural significance of traditional foods in an economically, socially, and environmentally sustainable manner. This involves the intergenerational transmission and deep cultural ties associated with these foods. Regional agricultural biodiversity and production techniques play a crucial role in maintaining traditional knowledge and sustainable resource utilization. However, a key challenge lies in encouraging younger generations to embrace these products amidst evolving market dynamics. Their involvement is pivotal in passing down traditional food knowledge and safeguarding cultural heritage. Efforts must be directed toward promoting the nutritional, ecological, and sustainable dietary benefits of traditional foods. Integrating traditional crops into the food system holds promise for a sustainable and nourishing food system, addressing employment and environmental goals.